Docetaxel-induced radiation recall dermatitis with atypical features: A case report - Sakaguchi, Masakuni (Medicine (Baltimore), 2018)
INTRODUCTION: Radiation recall dermatitis (RRD) associated with actinomycin D was first described by in 1959, followed by the reporting of several RRD-inducing drugs. In 1994, a study demonstrated docetaxel-induced RRD for the first time; however, despite some case studies reporting RRD, a little has been reported on it since then. Here we present a rare case of atypical docetaxel-induced RRD. CASE PRESENTATION: The patient in his 60s was administered radiotherapy for high-risk prostate cancer. He continued receiving hormonal therapy for 2 years because of being in a high-risk group and became nadir. Six months since the completion of hormonal therapy, his prostate-specific antigen (PSA) level increased again. Based on the radiological examination, he was diagnosed with multiple lung, bone, and lymph node metastases. Accordingly, we started docetaxel (75 mg/m(2)) every 5 weeks in consideration of myelosuppression for hormone-resistant multiple metastases. Although lung metastasis shrunk by one cycle docetaxel, radiotherapy for the thoracic and lumbar vertebrae was performed for back pain and lumbago. On day 21, at the end of radiotherapy, the same dose of docetaxel was administrated for the third time. On day 7, after third docetaxel administration, erythema appeared in a irradiated field of the thoracic and lumbar vertebra. Erythema primarily appeared on the anterior side of the body, and no skin reaction was noted on the posterior part of the thoracic irradiated area. Notably, no skin reaction was observed in the previously irradiated field for prostate cancer. CONCLUSIONS: This case report draws attention to the development of atypical RRD after administration of docetaxel and advises careful follow-up even if RRD does not appear after the first docetaxel administration.